KEKUATAN MENGIKAT PERJANJIAN YANG DIBUAT SECARA LISAN - Ridoli Sitompul, Fajar Sahat; Ariani, I Gusti Ayu Agung (Kertha Semaya : Journal Ilmu Hukum, 2014)
Agreement is a an activity commonly conducted by society to initiate term and condition regarding trade activity, lending and others business activity. Agreement could be conducted verbally and written. Verbal agreement also commonly known as gentlemen agreement conducted in traditional society to conservatively bonding the commitment between one party to another party. Meanwhile the written agreement were conducted by the modern society regarding business matter with sophisticated legal system. The discussion in these research will show the commitment that bond a agreement. The purpose of this literature to acknowledge the commitment capacity of the verbal agreement that made by stake holder. The method that will used in these research is Normative method, in which we will focused on the legal Principe also to analyze the written laws. In the practice the verbal agreement is a agreement that had to be fulfilled by the stakeholder due to the dealing term that already made by the stake holder. With strong legal basis the stake holder were expected to fulfill the right and obligation from what already been committed.
Keywords: Commitment, Written agreement